2022
DOI: 10.1002/dmrr.3559
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid versus metabolic syndrome as markers of fatty liver disease in young people with overweight/obesity

Abstract: Aims:To compare the association of high serum uric acid (HUA) or metabolic syndrome (MetS) with fatty liver disease (FLD) in youths with overweight/obesity (OW/OB). Materials and Methods: Cross-sectional study of anthropometrics, biochemical variables, and liver ultrasound of 3104 individuals with OW/OB (age 5-17 years). Metabolic syndrome was defined by ≥ 3 criteria among (1) high waist circumference; (2) high triglycerides; (3) low high-density lipoproteins; (4) fasting glucose ≥100 mg/ dl; (5) blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Again, obese children with MetS were found to have significantly higher urinary BPA levels than obese children without MetS and in both obese groups levels were higher than in healthy controls [ 66 ]. Bisphenols may also affect uric acid metabolism, and this aspect is of concern, as a potential relationship between hyperuricemia and hypertension, MetS, fatty liver disease, and cardiovascular disease in pediatric populations has been identified [ 67 , 68 , 69 ]. The associations between BPA, bisphenol S (BPS), and bisphenol F (BPF) exposure and serum uric acid concentrations were evaluated in the Environment and Development of Children cohort study, encompassing 489 six-year-old Korean children.…”
Section: Resultsmentioning
confidence: 99%
“…Again, obese children with MetS were found to have significantly higher urinary BPA levels than obese children without MetS and in both obese groups levels were higher than in healthy controls [ 66 ]. Bisphenols may also affect uric acid metabolism, and this aspect is of concern, as a potential relationship between hyperuricemia and hypertension, MetS, fatty liver disease, and cardiovascular disease in pediatric populations has been identified [ 67 , 68 , 69 ]. The associations between BPA, bisphenol S (BPS), and bisphenol F (BPF) exposure and serum uric acid concentrations were evaluated in the Environment and Development of Children cohort study, encompassing 489 six-year-old Korean children.…”
Section: Resultsmentioning
confidence: 99%
“…Civantos Modino S (29) discovered that overweight and obese children had higher average SUA levels, and this group had a higher probability of having metabolic syndrome. It is worth mentioning that SUA, as a marker for predicting fatty liver risk in adolescents, is more discriminative than metabolic syndrome (30) In a retrospective study, the risk of dyslipidemia increased by 27% for each 1-SD increase in SUA in children with adenoid or tonsil hypertrophy. There was a signi cant positive association between SUA and HTG (31)…”
Section: Discussionmentioning
confidence: 96%
“…Civantos Modino S [ 39 ] reported that overweight and obese children exhibited elevated average SUA levels, which significantly increased their likelihood of developing metabolic syndrome. Notably, SUA serves as a superior marker for predicting fatty liver risk in adolescents compared to metabolic syndrome itself [ 40 ]. In a retrospective analysis of 4,922 children diagnosed with adenoid or tonsil hypertrophy, a one standard deviation increase in serum uric acid (SUA) was associated with a 27% increased risk of dyslipidemia, with an OR of 1.270 and a 95% CI ranging from 1.185 to 1.361.…”
Section: Discussionmentioning
confidence: 99%